Hydraulic Fracturing and Rock Mechanics - Zhao, Yu; Zhang, Yongfa; He, Pengfei (Springer Nature, 2023)
This open access book is the first to consider the effect of non-uniform fluid pressure in hydraulic fractures. The book covers the key topics in the process of hydraulic fracture nucleation, growth, interaction and fracture network formation. Laboratory experiments and theoretical modeling are combined to elucidate the formation mechanism of complex fracture networks. This book is suitable for master’s/Ph.D. students, scientists and engineers majoring in rock mechanics and petroleum engineering who need to use a more reliable model to predict fracture behavior.